HPV antibody levels and clinical efficacy following administration of a prophylactic quadrivalent HPV vaccine (2008)
The efficacy of the quadrivalent Human Papillomavirus (HPV) vaccine is thought to be mediated by humoral immunity. We evaluated the correlation between quadrivalent HPV vaccine-induced serum anti-HPV responses and efficacy. 17,622 women were vaccinated at day 1, and months 2 and 6. At day 1 and at 6-12 months intervals for up to 48 months, subjects underwent Papanicolaou and genital HPV testing. No immune correlate of protection could be found due to low number of cases. Although 40% of vaccine subjects were anti-HPV 18 seronegative at end-of-study, efficacy against HPV 18-related disease remained high (98.4%; 95% CI: 90.5-100.0) despite high attack rates in the placebo group. These results suggest vaccine-induced protection via immune memory, or lower than detectable HPV 18 antibody titers. © 2008 Elsevier Ltd. All rights reserved.